O kryteriach wyodrębniania terminów z XVI-wiecznych tekstów - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article aims to present a method for identifying and extracting terms from sixteenth- century texts based on four criteria: a) textual – assuming that if a semantic unit’s meaning is confirmed only in texts characteristic of a specific field of science or knowledge, then it is a term of that period; b) linguistic – based on the information about the semantic unit originating from prestigious languages (Latin or/and Greek) and provided by the author; c) disciplinary – based on the information about the semantic unit being used by a specific professional group and provided by the author; d) linguistic and disciplinary (which combines criteria 2 and 3).